2019
DOI: 10.2174/1874205x01913010072
|View full text |Cite
|
Sign up to set email alerts
|

E200k Familial Creutzfeldt-Jakob Disease Presenting with Subacute Multiple Cranial Neuropathy

Abstract: Unusual clinical presentations in patients with E200K familial Creutzfeldt-Jakob Disease (fCJD) have been rarely reported. Herein, we described a case of E200K fCJD presenting with subacute cranial multiple neuropathy, initially suspected to be paraneoplastic or due to a leptomeningeal carcinomatosis, considering the neoplastic comorbidity of the patient. Surprisingly, brain MRI was highly suggestive of CJD. Brain histological examination confirmed the diagnosis. Genetic tests led to the definite diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This is supported by previous studies, which showed wide variation of PrP expression in healthy control brains [ 23 ]. This may explain why some carriers of the E200K mutation do not develop the disease as well as why the clinical signs [ 24 ], age of clinical onset, and duration of clinical disease vary between individuals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous studies, which showed wide variation of PrP expression in healthy control brains [ 23 ]. This may explain why some carriers of the E200K mutation do not develop the disease as well as why the clinical signs [ 24 ], age of clinical onset, and duration of clinical disease vary between individuals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%